End-of-Life and Palliative Care in a Critical Care Setting: The Crucial Role of the Critical Care Pharmacist - Rhona Sloss; Reena Mehta; Victoria Metaxa (MDPI AG, 2022)
Critical care pharmacists play an important role in ICU patient care, with evidence showing reductions in drug prescribing errors, adverse drug events and costs, as well as improvement in clinical outcomes, such as mortality and length of ICU stay. Caring for critically ill patients around the end of their life is complicated by the acute onset of their illness and the fact that most of them are unable to communicate any distressing symptoms. Critical care pharmacists are an integral part of the ICU team during a patient's end-of-life care and their multifaceted role includes clinical support for bedside staff, education, and training, as well as assistance with equipment and logistics. In this article, we highlight the important role of the ICU pharmacist using a 'real-life' clinical case from our hospital.